Determination of the Compensatory Growth Response, Mineral and Antioxidant Enzyme Activities of European Sea Bass Fingerlings (Dicentrarchus labrax) in Fasting and Re-feeding - Dernekbaşı, Seval; Kaya Öztürk, Dilara; Yürüten Özdemir, Keriman; Karayücel, İsmihan (Canakkale Onsekiz Mart University, 2025)
Understanding compensatory growth in European sea bass (Dicentrarchus labrax) is also crucial for optimizing aquaculture practices as it can lead to more efficient feeding strategies and improved fish health. To this end, this study evaluated the effects of fasting and re-feeding on growth performance, mineral and antioxidant enzyme activities of European sea bass fingerlings. The experiment involved five treatments, each with three replicates. The control treatment was fed continuously, while treatments A1, A2, A3, and A4 were fasted for one, two, three, and four weeks, respectively. Following the fasting period, all treatments were fed to satiation twice daily for four weeks. At the end of the trial, the control treatment showed the best growth during the fasting period, while the growth of the other treatments decreased with the duration of fasting (p
Keywords: fasting; antioxidant enzymes; european sea bass; Aquaculture. Fisheries. Angling; compansatory growth; SH1-691; re-feeding; dicentrarchus labrax; mineral matters